2023
DOI: 10.1037/cap0000360
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic test of the efficacy of cognitive behavioural therapy for perfectionism: A replication and extension.

Abstract: Meta-analyses conclude that cognitive behavioural therapy (CBT) for perfectionism is efficacious without addressing indices of efficacy such as reliable improvement, deterioration, dropout, and change at follow-up. We addressed this through a reanalysis of the 16 randomized controlled trials included in Galloway et al. (2022), Robinson andWade (2021), andSuh et al. (2019). At posttreatment, small-to-large effects favouring CBT were found for certain perfectionism measures: high standards (g = −0.40), doubts ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(35 citation statements)
references
References 81 publications
0
34
0
1
Order By: Relevance
“…The definition of dropout used, that is, "all randomized participants who did not complete posttreatment measures regardless of whether they started treatment or the reason for dropout" (p. 358) combines "decliners" who verbally accept randomization but do not attend the first session (e.g., because they were randomized to a condition they did not like), "dropouts" who had at least one session but fewer than the number of sessions defined as therapy completion, and "no shows" who completed treatment but for various reasons failed to come to postassessment. While study dropout for any reason has been used in some meta-analyses, this reflects dropout, not tolerance, as Smith et al (2023) incorrectly conclude.…”
Section: Dropout and Treatment Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…The definition of dropout used, that is, "all randomized participants who did not complete posttreatment measures regardless of whether they started treatment or the reason for dropout" (p. 358) combines "decliners" who verbally accept randomization but do not attend the first session (e.g., because they were randomized to a condition they did not like), "dropouts" who had at least one session but fewer than the number of sessions defined as therapy completion, and "no shows" who completed treatment but for various reasons failed to come to postassessment. While study dropout for any reason has been used in some meta-analyses, this reflects dropout, not tolerance, as Smith et al (2023) incorrectly conclude.…”
Section: Dropout and Treatment Tolerancementioning
confidence: 99%
“…Omission of Studies That Were Included in the Previous Meta-Analyses Which Were Reexamined Smith et al (2023) state that their meta-analysis is a replication and extension of three previous meta-analyses (Galloway et al, 2022;Robinson & Wade, 2021;Suh et al, 2019); however, it is problematic that they omitted two previous randomized controlled trials (RCTs;Pleva & Wade, 2007;Wilksch et al, 2008) that were included in these meta-analyses, despite their footnote that they did not exclude any studies. The three previous systematic reviews Smith et al (2023) aimed to replicate (Galloway et al, 2022;Robinson & Wade, 2021;Suh et al, 2019) applied different inclusion and exclusion criteria across the reviews, searched for studies with different outcomes, searched in different databases, some but not all included the gray literature, and have different search dates. Therefore, simply equating the studies included in independent systematic reviews into one's own review and metaanalysis is not a standardized strategy.…”
mentioning
confidence: 99%
“…This randomized controlled feasibility study found further support for the EFI derived from the PCPM (Dunkley, 2017), with individualized feedback delivered in-person and online by student research assistants to individuals with higher SC perfectionism. Considering that longer perfectionism interventions (Shafran et al, 2023) are not well tolerated by many individuals with perfectionism (Smith et al, 2023), our findings suggest that the single-session PCPM-EFI can have broad applicability, conceptual utility, and effectiveness for perfectionistic individuals.…”
Section: Discussionmentioning
confidence: 87%
“…The single-session EFI might instigate and support important processes of change and allow for more effective tailoring of therapeutic interventions (Schleider et al, 2020), rather than relying on symptom-based, "one size fits all" treatment protocols characterized by extreme comprehensiveness (e.g., CBT). The EFI might also help focus CBT interventions for perfectionism on one to three treatment elements rather than eight or more separate modules, which require sustained effort over several weeks (Shafran et al, 2023), resulting in low engagement and dropout (Smith et al, 2023). The feedback entertaining multiple mechanisms at multiple levels has the advantage of increased flexibility in interventions (e.g., shifting between different mechanisms to align with the situation and/or individual preferences; Kuyken et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation